The effect of intellectual property boxes on innovative activity & effective tax rates - Tobias Bornemann; Stacie K. Laplante; Benjamin Osswald (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
We investigate whether the adoption of an intellectual property box increases innovative activity and what type of firms benefit. We examine the adoption of the intellectual property box in Belgium because it allows us to cleanly identify the impact on innovative activity and effective tax rates. Our results indicate an overall increase in innovative activity as proxied by patent grants, the efficiency with which firms apply for and receive patents, and employment. We also provide evidence that, while firms with patents on average enjoy lower effective tax rates, the greatest financial benefits accrue to multinational firms without income shifting opportunities, followed by domestic firms. Multinational firms with income shifting opportunities do not significantly benefit from the intellectual property box.
Keywords: H21; H25; 330; IP boxes; tax incentive; tax avoidance; income shifting